Padding alloy and padding member

The new assemblage alloy with a specific composition addresses the issue of crack prevention in Cu-based alloys for substrate filling by reducing thermal expansion, thereby enhancing the integrity and wear resistance of the overlay portion.

JP2025040450APending Publication Date: 2025-03-25KK TOYOTA CHUO KENKYUSHO +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023147263
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing Cu-based alloys for filling substrates improve wear resistance and machinability but fail to prevent cracks that may occur during the overlay formation process.

Method used

A new assemblage alloy with a component composition of 20-30% Ni, 10-25% Fe, 5-15% Mo, and 1-3.5% Si, balanced with Cu and impurities, which reduces the coefficient of thermal expansion, thereby suppressing crack formation during the filling process.

Benefits of technology

The alloy effectively reduces thermal stresses and strains by minimizing dimensional changes in response to temperature variations, thereby preventing cracks and ensuring the integrity of the overlay portion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040450000001_ABST
    Figure 2025040450000001_ABST
Patent Text Reader

Abstract

To provide a new alloy capable of suppressing generation of cracking that can occur in a build-up process.SOLUTION: A padding alloy satisfies, when the whole alloy is defined as 100 mass% (hereinafter simply referred to as %), Ni:20-30%, Fe:10-25%, Mo:5-15%, Si:1-3.5%, and the balance Cu with impurities. Ni+Fe+Mo can, for example, be 46-52%. In this padding alloy, a thermal expansion coefficient in a temperature range (for example, 800°C) near a coagulation start is small, and thermal stress and strain introduced to a padding part are reduced. The padding part is composed of a metallographic structure in which hard particles are dispersed in a Cu-based matrix, and is superior also in abrasion resistance. The padding alloy can be a raw material powder before build-up, or a padding material obtained by build-up on a substrate using the raw material powder.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an alloy or the like used for build-up welding on a substrate. [Background technology]

[0002] Cladding is performed not only for the purpose of repairing the base material, but also to partially impart properties not found in the base material. One example is a valve seat formed by directly cladding a Cu-based alloy, which has excellent wear resistance, onto the valve seating portion of an Al alloy cylinder head using a laser cladding method or the like. This type of valve seat is advantageous in terms of design freedom around the valve train and cooling performance, compared to seat rings made of Fe-based sintered alloys that are press-fitted (hammered) into Al alloy cylinder heads.

[0003] Various Cu-based alloys for overlay welding have been proposed, and for example, there are related descriptions in the following patent documents. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2017-36470 (Patent No. 6396865) [Patent Document 2] Patent Publication No. 2018-58093 (Patent No. 6602737) [Patent Document 3] Patent Publication No. 2019-85626 (Patent No. 6675370) Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Documents 1 to 3, the component composition of the Cu-based alloy is determined merely for the purpose of improving the wear resistance and machinability of the cladding portion.

[0006] The present invention has been made in consideration of these circumstances, and aims to provide a new cladding alloy, etc. that not only improves wear resistance and machinability, but also can prevent cracks that may occur during the formation of the cladding portion. [Means for solving the problem]

[0007] The present inventors have conducted extensive research to solve the above problems and have developed a new build alloy with a different chemical composition from conventional ones. By further developing this result, the present invention, which will be described below, has been completed.

[0008] 《Overlay alloy》 (1) The cladding alloy of the present invention satisfies the following component composition, with the total being 100 mass % (hereinafter simply referred to as "%"). Ni:20~30%, Fe:10~25%, Mo:5~15%, Si: 1-3.5%, balance: Cu and impurities

[0009] (2) The weld overlay alloy of the present invention prevents cracks that may occur in the weld overlay or its periphery. The reason for this is presumed to be as follows.

[0010] Typically, the cladding alloy is rapidly heated by a high-energy beam or the like to form a molten portion (liquid phase), and then rapidly cooled by direct heat to the substrate to form a solidified portion (solid phase). Through this melting and solidification process (also called the "cladding process"), a cladding portion made of a cladding alloy of a predetermined composition is formed on the substrate.

[0011] The temperature of the substrate itself, except for the area near the interface where it comes into contact (bonds) with the cladding alloy, changes little or slowly during the cladding process. Therefore, after solidification is complete, thermal stress or strain occurs in the cladding and its surrounding area, depending mainly on the thermal expansion coefficient of the cladding and its temperature change. Of course, immediately after solidification begins or in a solid-liquid coexistence state, thermal stress and strain can also occur due to solidification shrinkage of the cladding.

[0012] The cladding alloy of the present invention has a relatively small coefficient of thermal expansion. In particular, the coefficient of thermal expansion is small in the temperature range where the above-mentioned thermal stress and strain begin to occur (for example, around 800°C). Therefore, the cladding portion of the present invention exhibits small dimensional changes with temperature changes, even in the high-temperature range of the cladding process where the temperature difference with the base material becomes large. As a result, the thermal stress and strain that occur in the cladding portion constrained by the base material and its surroundings (including the vicinity of the interface and the base material) during the cladding process are reduced, and cracks that may occur as a result of these are suppressed.

[0013] The present invention aims to reduce the thermal expansion coefficient of the cladding alloy (cladding portion) itself in order to prevent cracks that may occur during the cladding process. It has been confirmed that, including Cu-based alloys described in prior art documents, cracks that may occur in the environment in which the component is used (such as under thermal cycles) do not occur. The present invention also does not aim to reduce the difference in the thermal expansion coefficients of the cladding portion and the base material in order to prevent cracks that may occur in the environment in which the component is used.

[0014] Incidentally, since the alloy structure of a multi-element alloy (in this case, a quinary alloy consisting of five basic elements) is complex, it is difficult to predict its thermal expansion coefficient by numerical analysis based on the composition of each component. Therefore, in practice, the thermal expansion coefficient of a multi-element alloy can only be determined by actual measurement.

[0015] <Overlaying material> The present invention can also be understood as a cladding member. For example, the present invention may be a cladding member including an Al base material and a cladding portion formed on the base material, wherein the cladding portion is made of the cladding alloy described above.

[0016] <<Method for manufacturing cladding member>> The present invention can also be understood as a method for manufacturing a cladding member. For example, the present invention may be a manufacturing method for obtaining a cladding member using a raw material powder made of the cladding alloy described above. Specifically, the method can be implemented by, for example, a cladding method (laser cladding, etc.) or a directed energy deposition method (laser metal deposition, etc.) using a high-energy beam (laser light, electron beam, etc.) as a heat source.

[0017] "others" (1) The cladding alloy of the present invention may be in the form of a pre-cladding material or a cladding material after cladding. In other words, the cladding alloy may be a cladding raw material (powder, wire, etc.) or a cladding portion formed (melted and solidified) on a substrate.

[0018] (2) In this specification, "%" in relation to the composition means "mass %" unless otherwise specified. The cladding alloy of the present invention may contain trace amounts (for example, 1% or less in total) of modifying elements and impurities. In this specification, "X-based" or "X alloy" means that the X element is the most abundant (mass %) in the overall composition. The X element does not have to be the majority (more than 50 atomic %) of the overall composition.

[0019] (3) Unless otherwise specified, "x to y" in this specification includes a lower limit value x and an upper limit value y. Any numerical value included in the various numerical values ​​or numerical ranges described in this specification can be used as a new lower limit or upper limit value to create a new range such as "a to b." Unless otherwise specified, "α to β × 10" in this specification -5 / ℃ is α×10 -5 / ℃~β×10 -5 / ℃. The same applies to other units. [Brief explanation of the drawings]

[0020] [Figure 1] 1 shows SEM images and partially enlarged images showing the metal structure of the cladding portion of Samples 1, C1, and C8. [Figure 2] 1 is a photograph showing an ingot from which a test piece for measuring the thermal expansion coefficient was taken and a casting process for producing the ingot. DETAILED DESCRIPTION OF THE INVENTION

[0021] One or more components arbitrarily selected from the items described in this specification may be added to the above-described configuration of the present invention. A component related to a method may also be a component related to a product. Which embodiment is best depends on the target, required performance, etc.

[0022] 《Component composition》 The cladding alloy is a Cu-based alloy containing Ni, Fe, Mo, and Si. When melted, the Cu-based alloy generates, for example, at least two separate liquid phases. When such a two-liquid phase separation alloy melts and solidifies, for example, a composite structure is formed in which hard particles (hard phases) are dispersed in a Cu-based matrix.

[0023] Ni and Si mainly form the Cu-based matrix together with Cu. Fe and Mo form hard particles together with Si (and Ni). The specific composition ranges of each element are as follows. Unless otherwise specified, the composition is shown as a mass percentage (simply expressed as "%)" of the entire alloy.

[0024] The Ni content is, for example, 20 to 30%, 21 to 25%, 21.5 to 24%, or 22 to 23%. Ni contributes to reducing the thermal expansion coefficient of the Cu-based alloy and can increase its strength by dissolving in the Cu-based matrix. If the Ni content is too low, this effect is insufficient, while if the Ni content is too high, the tendency for two-liquid phase separation decreases, leading to refinement of hard particles (and ultimately to a decrease in the wear resistance of the cladding).

[0025] The Fe content is, for example, 10 to 25%, 15 to 20%, or 16 to 18%. Fe can contribute to reducing the thermal expansion coefficient of the Cu-based alloy and also to generating hard particles. If the Fe content is too low, this effect is insufficient, resulting in a decrease in the wear resistance of the cladding. If the Fe content is too high, the machinability can decrease.

[0026] The Mo content is, for example, 5 to 15%, 7 to 12%, 7.5 to 11%, or even 8 to 10.5%. Mo can also contribute to the reduction of the thermal expansion coefficient of Cu-based alloys and the generation of hard particles. Mo repels Cu even at high temperatures, contributing to the generation of a two-liquid phase separation state. Mo can improve the wear resistance of the cladding because its oxide has self-lubricating properties. If Mo is too little, these effects are insufficient, while if Mo is too much, it can lead to coarsening of hard particles and reduced machinability.

[0027] Ni, Fe, and Mo are all effective in reducing the thermal expansion coefficient of Cu-based alloys. Their total (Ni + Fe + Mo) may be, for example, 46 to 52%, 46.5 to 51.5%, or 47 to 51%. However, if the total is too large, it becomes difficult to produce the desired two-liquid phase separation state metal structure.

[0028] The Si content is, for example, 1 to 3.5%, 1.5 to 3.2%, or 2 to 3%. Si contributes to strengthening the Cu-based matrix or improving build-up properties. Si forms silicides with Fe and Mo, contributing to the formation of hard particles. If the Si content is too low, this effect is poor, and if the Si content is too high, machinability may decrease.

[0029] The cladding alloy of the present invention may contain modifying elements to the extent that they do not affect the above-mentioned composition. For example, the Cu-based alloy may contain 0.01-0.5% C, 0.1-1% Co, and 0.5-2% Cr. The total content of the modifying elements and unavoidable impurities is, for example, 2% or less, 1% or less, or 0.5% or less.

[0030] 《Metal structure》 A cladding portion having a metal structure in which hard particles are dispersed in a Cu-based matrix can exhibit excellent wear resistance. The metal structure (volume ratio (area ratio) of hard particles, their maximum diameter, etc.) reflects the state at the time of melting (two-liquid phase separation state, etc.). The metal structure and its properties are described in detail in JP 2019-85626 A (the aforementioned Patent Document 3) and the like, and the contents of that description are incorporated herein as appropriate.

[0031] The hard particles have a higher hardness than the Cu-based matrix, but the specific hardness is not important. The copper-based matrix may have a hardness of, for example, 150 to 350 Hv or 200 to 300 Hv. The hard particles may have a hardness of, for example, 650 to 1500 Hv or 700 to 1200 Hv. The hard particles may have multiple phases (hard phase and soft phase) with different hardnesses.

[0032] 《Base material》 The mating material (base material) to be built up may be a non-ferrous material (aluminum-based material, magnesium-based material, titanium-based material, copper-based material, etc.) or an iron-based material (including stainless steel).

[0033] A typical example is an Al substrate made of pure Al or an Al alloy. The Al substrate may be a cast material (including a die-cast material) or a wrought material. The Cu-based alloy does not react excessively with the Al substrate, and forms a sound cladding portion with few defects (voids, cracks, etc.).

[0034] <Overlaying material> An example of a cladding member in which a cladding portion is formed on a substrate is a valve seat. The valve seat is formed on the outer peripheral edge (valve seat) of the intake port and / or exhaust port of an aluminum alloy cylinder head (substrate) of an internal combustion engine.

[0035] 《Method of overlaying》 One example of a cladding method is a cladding method using a high-density energy beam (heat source). A laser is usually used for the high-density energy beam. The laser may be a carbon dioxide laser, a YAG laser, or a semiconductor laser with excellent controllability.

[0036] When the molten pool in the two-liquid phase separation state is vigorously stirred and rapidly cooled, a metal structure in which roughly spherical hard particles are uniformly dispersed in a Cu-based matrix is ​​obtained. This vigorous stirring can be achieved, for example, by periodically or intermittently changing the intensity or output of the laser irradiated onto the raw material powder. An oscillator, such as those described in Japanese Patent No. 4114922 or Japanese Patent No. 4472979, may also be used.

[0037] The build-up material is supplied in the form of, for example, a wire, a rod, or a powder. The powder material may be supplied with its particle size adjusted. The raw material powder may be a single powder or a mixed powder containing multiple types of powders with different component compositions, particle size distributions, etc.

[0038] <Coefficient of thermal expansion> The thermal expansion coefficient of the cladding usually changes with temperature. The thermal expansion coefficient of a Cu-based alloy generally increases monotonically with temperature. As an example, the thermal expansion coefficient at 800°C is, for example, 1.45 to 1.67 (×10 -5 / ℃), 1.47 to 1.66 (×10 -5 / ℃) or 1.50 to 1.65 (×10 -5 / ℃). [Example]

[0039] A number of different raw material powders (cladding alloys) with different component compositions were prepared, and the metal structures of claddings (samples) formed using these powders were observed. The thermal expansion coefficients of test pieces made using each raw material powder were also measured. The present invention will be explained in more detail based on these specific examples.

[0040] 《Metal structure》 (1) Raw materials As raw materials, several gas atomized powders with different compositions were prepared. The gas atomized powders were produced by spraying molten alloy prepared at 1800°C into an inert gas atmosphere. The obtained gas atomized powders were classified by sieving into particle sizes of 32 to 180 μm and used for overlay welding. The composition shown in Table 1 was obtained by analyzing a portion of the ingot described below.

[0041] (2) Base material A cylindrical substrate (φ60 mm × height 30 mm) made of aluminum alloy (JIS AC2B) was prepared.

[0042] (3) Meat platter Each raw material powder was supplied to a laser cladding device (manufactured by Laserline) that uses a semiconductor laser beam (LD) as a heat source, and cladding was performed on the substrate. The laser output was 2.9 kW, the scanning speed was 900 mm / min, and the atmosphere was N2 flow. The raw material powder was heated to approximately 1500°C or higher, and separated into two liquid phases. It was then rapidly cooled and solidified on the substrate to form the cladding. The cross section of the cladding was approximately semicircular (thickness: approximately 2 mm, width: approximately 4 mm).

[0043] (4) Observation The overlay welds embedded in epoxy resin were mirror-polished and their metal structures were observed using a scanning electron microscope (SEM). The metal structures of some of the samples are shown in Figure 1. In all samples, a metal structure with hard particles (white areas) dispersed in a Cu-based matrix was observed. For reference, the size of the hard particles observed in the metal structure of each sample is shown in Table 1, divided into three stages (fine < standard < coarse).

[0044] <Coefficient of thermal expansion> (1) Test piece The thermal expansion coefficient was measured using test pieces (φ6 mm × length 20 mm) taken from the rapidly solidified ingot, because it was not possible to take test pieces of the size required for measurement from the overlay portion.

[0045] The ingots were produced as follows: the raw material powders for each sample were vacuum melted, and the molten metal (1650°C) was poured into a carbon mold placed on a copper plate in an Ar atmosphere. Test pieces to be used for measuring the thermal expansion coefficient were taken from the bottom (copper plate side) of the ingot, where the solidification rate was fastest. This casting process and the locations where the resulting ingots and test pieces were taken are shown in Figure 2.

[0046] (2) Measurement Each test piece was set in a horizontal bar type thermal expansion measuring device (TD5000SA manufactured by NETZSCH) and measured in accordance with JIS Z2285. Specifically, the measurement was carried out as follows.

[0047] The longitudinal displacement of the test piece heated from room temperature to 800°C in an Ar gas atmosphere was measured using a horizontal differential detection method. The average thermal expansion coefficient for every 100°C was calculated using the following formula from the average displacement (N=2) obtained from two measurements. Table 1 shows the average thermal expansion coefficient at 800°C. Average thermal expansion coefficient ( / ℃) = {(L1-L0) / L0} / (T1-T0) T1: Measurement temperature (100~800℃), T0: Reference temperature (30℃) L1: length of specimen at T1, L0: length of specimen at T0

[0048] For reference, the rate of change (%) in the thermal expansion coefficient (800°C) based on sample C8 is also shown in Table 1. Sample C8 was prepared with reference to the description in JP 2019-85626 A (the above-mentioned Patent Document 3).

[0049] "evaluation" (1) Metal structure As can be seen from Figure 1, a metal structure in which hard particles are dispersed in a Cu-based matrix was observed in all samples. The build-up portion with such a metal structure has excellent wear resistance, for example.

[0050] (2) Thermal expansion coefficient As can be seen from Table 1, only the samples whose component compositions were within a specific range showed a relatively large decrease in the thermal expansion coefficient. This is also evident from the rate of increase or decrease in the thermal expansion coefficient shown in Table 1 (samples 1 to 4).

[0051] The inventors have conducted a CAE (Computer Aided Engineering) analysis and confirmed that when the thermal expansion coefficient at 800°C is sufficiently small (for example, when the rate of increase or decrease shown in Table 1 is -5% or less), strain, which is a factor in the generation of cracks that can occur during the build-up process, is reduced, and that cracks will not occur when actual parts are manufactured.

[0052] From the above, it was confirmed that the cladding alloy of the present invention can suppress factors that may cause cracks during the cladding process.

[0053] [Table 1]

Claims

1. A weld overlay alloy that satisfies the composition shown below, with the total being 100 mass% (hereinafter simply referred to as "%"). Ni: 20-30%, Fe: 10-25%, Mo: 5 to 15%, Si: 1-3.5%, Remainder: Cu and impurities

2. The cladding alloy according to claim 1 , wherein the component composition (%) satisfies the following formula: 46≦Ni+Fe+Mo≦52

3. A build-up alloy that satisfies the composition shown below, taking the whole as 100%. Ni: 21-23%, Fe: 16-18%, Mo: 7.5-11%, Si: 1.5-3.2%, Remainder: Cu and impurities

4. The cladding alloy according to claim 3, wherein the component composition (%) satisfies the following formula: 47≦Ni+Fe+Mo≦51

5. It is a two-liquid phase separation type alloy that can produce two separate liquid phases. The cladding alloy according to any one of claims 1 to 4.

6. The cladding alloy according to any one of claims 1 to 4, which is cladded onto an Al base material.

7. An Al base material; A cladding portion formed on the Al base material, A cladding member, wherein the cladding portion is made of the cladding alloy according to any one of claims 1 to 4.

8. The cladding member according to claim 7, wherein the cladding portion has a metal structure in which hard particles containing Mo are dispersed in a Cu-based matrix.

9. 9. The cladding member according to claim 8, wherein the cladding portion forms a valve seat of an internal combustion engine.

Citation Information

Patent Citations

  • Dry cell

    JP1988096865A

  • Abrasion resistant copper base alloy

    JP2017036470A

  • Padding alloy and padding member

    JP2018058093A

  • Hardfacing alloy and hardfacing member

    JP2019085626A

  • Overlay alloys and overlay components

    JP6602737B2